Coagulation/anticoagulation-regulable and tough extracellular matrix hydrogels. (15th June 2022) - Wang, Fangfang; Zhang, Rui; Gao, Niuniu; Chang, Chunyu; Wang, Zonghuan; Zhou, Yingjie; Zhang, Chi; Ma, Jianwei; Jin, Yong; Wei, Peng; Mei, Jin
Abstract: Many active proteins and growth factors exist in extracellular matrix (ECM), regulating important physiological processes in the body. The conversion of ECM into hydrogels will significantly expand their application scope. Given the complexity of the environment in vivo, fabrication of ECM hydrogels with regulable coagulation/anticoagulation is very important yet challenging. Herein, we utilize phosphate buffer (PBS) as a concentration switch to realize the coagulation/anticoagulation transformation of ECM hydrogels. Benefiting from their regulable characteristic, these ECM hydrogels are respectively converted into hemostatic sponges/powders and tough anticoagulant films. The tensile strength of the film reached 39.23 ± 3.21 MPa. Especially, blood flow signals were still detected after two weeks transplantation of ECM films onto rat carotid arteries (diameter < 1 mm) as a vascular patch, suggesting the potential application of ECM anticoagulant films in small-caliber vascular grafts. This work provided a facile and sustainable strategy for developing ECM hydrogels with regulable coagulant/anticoagulant properties. Graphical abstract: Image 1